Asociación entre diabetes mellitus e insuficiencia arterial cavernosa en pacientes con disfunción eréctil - Hernandez-Yepez, PJ (2023)
Introduction: Erectile dysfunction is highly prevalent in the population and vascular and neural processes are involved in its pathophysiology, including those related to late complications of diabetes mellitus. Objective: To determine the association between diabetes mellitus and corpus cavernosum arterial insufficiency in patients with erectile dysfunction. Methods: Cross-sectional study of secondary data analysis conducted in a private health facility in Lima during the year 2022. Patients with a confirmed diagnosis of erectile dysfunction were included. The independent variable was the diagnosis of diabetes mellitus and the dependent variable was the diagnosis of corpus cavernosum arterial insufficiency. Association statistics were performed and prevalence ratios were estimated using logistic regression. Results: Of 887 patients, the mean age was 48.5 years. In the bivariate analysis, an association was found between diabetes mellitus and corpus cavernosum arterial insufficiency (p< 0.001). In the simple regression analysis, the prevalence of having corpus cavernosum arterial insufficiency was 92% higher in patients who had diabetes mellitus (OR: 1.92; 95% CI: 1.75-2.11; p< 0,001). Conclusions: There is an association between diabetes mellitus and corpus cavernosum arterial insufficiency in patients with erectile dysfunction, the prevalence of corpus cavernosum arterial insufficiency was notably higher in patients with diabetes mellitus. © 2023, Editorial Ciencias Medicas. All rights reserved.